Guided routing on spinning microfluidic platforms1. Issue 12 (11th February 2015) - Kazemzadeh, Amin; Ganesan, P.; Ibrahim, Fatimah; Kulinsky, Lawrence; Madou, Marc J.
<x xml:space="preserve">Abstract</x> A robust two stage passive microvalve is devised that can be used for (a) changing the flow direction continuously from one direction to another, and (b) liquid/particle distribution in centrifugal microfluidics.